Conservation and management of livestock and poultry genetic resources - Bondoc, Orville L. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2000)
The paper reviews the biodiversity of livestock and poultry genetic resources in the Philippines, their importance, and threats to their irreversible loss. Animal breeding strategies are proposed and outlined. Some modern biotechnologies, their uses, advantages and disadvantages are also presented. These include the use of indirect predictors, marker loci, and reproductive biotechnologies (e.g., artificial insemination techniques; multiple ovulation and embryo transfer and related technologies; and molecular genetic manipulation). Much has already been done with regard to technical plans, policies and even legislation, along with characterization and documentation of livestock and poultry genetic resources in the country. Research on genetic resistance seems lacking. Actual conservation (not short-term research projects) in all species is yet to be demonstrated. Establishment of a modern laboratory is proposed to ascertain pedigree and certify native breeds and strains. Actual in-situ and ex-situ conservation in nucleus breeding units does not only make the applications of new biotechnologies relevant and meaningful but also ensures that real effort is being made to conserve, utilize, and improve them. The local program that seeks to conserve and manage them should consider the following: characterization and documentation; in-situ conservation; ex-situ conservation; communication and information system; collaboration, coordination, and policy advocacy. All these require substantial funds and technical support from government and private breeding companies or farmers' cooperatives on a long-term basis.